Preventive Migraine Treatment - Silberstein, Stephen D. (Continuum (Minneap Minn), 2015)
PURPOSE OF REVIEW: This article reviews the evidence base for the preventive treatment of migraine. RECENT FINDINGS: Evidence-based guidelines for the preventive treatment of migraine have recently been published by the American Academy of Neurology (AAN) and the Canadian Headache Society (CHS), providing valuable guidance for clinicians. Strong evidence exists to support the use of metoprolol, timolol, propranolol, divalproex sodium, sodium valproate, and topiramate for migraine prevention, according to the AAN. Based on best available evidence, adverse event profile, and expert consensus, topiramate, propranolol, nadolol, metoprolol, amitriptyline, gabapentin, candesartan, Petasites (butterbur), riboflavin, coenzyme Q10, and magnesium citrate received a strong recommendation for use from the CHS. SUMMARY: Migraine preventive drug treatments are underutilized in clinical practice. Principles of preventive treatment are important to improve compliance, minimize side effects, and improve patient outcomes. Choice of preventive treatment of migraine should be based on the presence of comorbid and coexistent illness, patient preference, reproductive potential and planning, and best available evidence.